Understanding the Drivers of Production in South African Farming Systems: A Case Study of the Vhembe District, Limpopo South Africa - Materechera, Fenji; Scholes, Mary Cathrine (Frontiers in Sustainable Food Systems, 2022)
Farming systems in South Africa operate against the backdrop of constantly changing environmental, political and socio-economic conditions. Farming systems are commonly defined by the FAO (2019) as a population of individual farm systems that have broadly similar resource bases, enterprise patterns, household livelihoods and constraints, and for which similar development strategies and interventions would be appropriate. Historically farming systems in South Africa have been characterized by a dualism in which large-scale commercial farmers co-exist with small-scale farmers and these can be found throughout the country. The two farming systems are impacted by the same drivers of production (land, labour, capital and enterprise) however they respond to these drivers differently, the nature of the response may reveal the connectivity between the systems. A systems thinking approach is best suited to illustrate the connectivity between the two farming systems and how the systems will respond to change in the future with respect to drivers. The Vhembe district located in the Limpopo Province of South Africa serves as a noteworthy example of the co-existing farming systems. Large-scale commercial farming forms a significant component of the production of a number of subtropical crops that contribute to the country’s agricultural economy particularly through exports. Simultaneously 90% of rural communities in the district depend mainly on small-scale agriculture to sustain their livelihoods and generate income. The chapter provides an overview of the drivers of production for the two farming systems in the Vhembe district and explores the connectivity between the systems with respect to drivers.